Analysis of fatal outcomes from in?uenza A(H1N1)pdm09 in Mongolia - Baigalmaa, Jantsansengeegiin; Tuul, Tseesurengiin; Darmaa, Badarchyn; Soyolmaa, Erdenebaatariin (Western Pacific Surveillance and Response, 2013)
Introduction: While influenza A(H1N1)pdm09 usually causes mild illness in the majority of people, there have been reports of severe cases and deaths. As there is no documented evidence on fatal outcomes from influenza in Mongolia previously, we aimed to describe the epidemiology of fatal influenza A(H1N1)pdm09 cases to provide recommendations to assist the national influenza prevention and control strategy.Methods: We selected influenza A(H1N1)pdm09-confirmed deaths in hospitals between 12 October 2009 and 31 January 2010 in Mongolia from the national influenza surveillance system. The mortality rate and case fatality rate (CFR) of influenza A(H1N1)pdm09-hospitalized deaths were calculated. Using country prevalence of pregnancy and chronic diseases, we calculated the relative risk of death from influenza A(H1N1)pdm09.Results: There were 29 deaths with a mortality rate of 1.0 per 100 000 population during the study period, which was highest in children under five and the middle-aged population. Crude CFR was 2.2%. Of all fatal cases, 62% had at least one underlying condition. Most (62%) were provided antivirals, although none received these within 48 hours of symptom onset. Prevalence for pregnancy, cardiovascular and chronic liver diseases was five to 50 times higher in fatal cases compared to country prevalence.Discussion: Mortality and crude CFR in our study was higher than in other studies. However, due to the diagnostic policy change during the epidemic, this estimate is likely to have overestimated actual case fatalities. Pregnancy, cardiovascular and chronic liver diseases were suggestive risk factors for death from influenza A(H1N1)pdm09. Strengthening hospital-based influenza surveillance is important in predicting severity of an epidemic and responding to influenza epidemics in a timely and appropriate manner.